Beyond job description: Cultivating public sector citizenship behavior through growth mindset and thriving at work - Ridian Khasanah; Alice Salendu; Putri Ramadhani Salim (Jurnal Psikologi Tabularasa, 2026)
Research on Organizational Citizenship Behavior (OCB) among Indonesian civil servants plays a key role in enhancing the quality of innovations, as prior studies reflect growth mindset ability to predict the emergence of OCB. Following Conservation of Resources (COR) theory, the psychological mechanism underlying this relationship is examined through Thriving at Work (TAW) as a mediator. This study examined the mediating effect of TAW on the association between growth mindset and OCB with a quantitative method with cross-sectional survey design. Using convenience and snowball sampling methods, participants of this study were 163 civil servants (PNS SDM IPTEK) of Organization X. The research instruments were adaptation of psychological scales with proven reliability. The data was analyzed using Macro PROCESS by Hayes in SPSS version 29, showed TAW partially mediates the relationship between growth mindset and OCB. This study has potential further implementations in Indonesia's public sector to drive positive work behavior (OCB) through maintaining a positive mindset (growth mindset) among the civil servants.